Internal Force Response of a Pile in an Inhomogeneous Temperature Field - Dan Zhang (Energies, 2017)
An inhomogeneous temperature field was built in an experimental model of sand with an embedded pile. The temperature of the soil, as well as the temperature and strain on opposite sides of the pile were investigated in the process of temperature balance. The effect of the inhomogeneous temperature field on the internal force of the pile was analyzed. The experimental results show that the inhomogeneous temperature field will cause a bending deformation in the pile body according to the FBG (fiber Bragg grating) strain sensors. The distribution of the bending moment along the length of the pile is related to the temperature difference. The maximum bending moments reached −25.7 N·m when the temperature difference was about 1.3 °C. Therefore, the influence of the inhomogeneous temperature field o· the internal force of the foundation pile should be taken into account in the applications of a ground source heat pump system.